Analisis ANALISIS PORTOFOLIO OPTIMAL PADA INVESTASI LOGAM MULIA EMAS MENGGUNAKAN METODE MEAN ABSOLUTE DEVIATION (MAD) DENGAN ESTIMASI PARAMETER GARCH(1,1) - VERENNIKA, FEBBY; DHARMAWAN, KOMANG; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2024)
This study aims to analyze the optimal portfolio in gold precious metal investments using the Mean Absolute Deviation (MAD) method combined with the GARCH(1,1) parameter estimation. The MAD method was chosen for its ability to measure portfolio risk more stably and simply compared to other methods like Mean-Variance. Meanwhile, the GARCH(1,1) model is used to estimate the volatility of gold prices, which are often influenced by global economic and geopolitical uncertainties. The data used in this study include daily stock prices of gold companies from January 2017 to June 2021. The analysis results show that the combination of the MAD method and GARCH(1,1) can provide a more comprehensive view of forming an optimal portfolio that maximizes returns and minimizes risks for gold investors. Based on the calculations, the optimal portfolio with the best performance was identified using the Sharpe, Treynor, and Jensen indices, which indicate the superiority of the first portfolio in terms of return and risk.